First record of the Combtooth Blenny, Microlipophrys adriaticus (Steindachner & Kolombatovic, 1883) (Pisces, Blenniidae), for the Italian Ionian Sea - F. Tiralongo; R. Baldacconi (Check List, 2015)
Microlipophrys adriaticus (Steindachner & Kolombatovic, 1883) is an endemic blenny of the Mediterranean Sea. It is also known from the Sea of Marmara and the Black Sea. However, unlike other species of combtooth blennies, M. adriaticus is a fish with a limited distribution in Adriatic Sea, especially in the north, where it can be common. We report here the first record of this species from the waters of the Ionian Sea.